2020
DOI: 10.1186/s13075-020-02297-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased high molecular weight adiponectin and lean mass during tocilizumab treatment in patients with rheumatoid arthritis: a 12-month multicentre study

Abstract: Background Patients with rheumatoid arthritis (RA) have an increased risk of cardiovascular (CV) disease. Adiponectin is involved in the metabolism of glucose and lipids with favourable effects on CV disease, especially its high molecular weight (HMW) isoform. Body composition changes are described in RA with various phenotypes including obesity. The effects of tocilizumab on serum adiponectin and body composition, especially fat mass, in patients with RA are not well determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 42 publications
2
28
1
8
Order By: Relevance
“…Of note, participants performed supervised high-intensity interval training in the latter study [ 9 , 10 ], whereas in the current study, they performed unsupervised continuous training [ 8 ], potentially explaining the divergent findings. However, in line with the data presented herein, tocilizumab significantly increased the serum adiponectin levels in patients with rheumatoid disease [ 11 , 12 ]. Of note, no placebo controls were included in the latter studies.…”
Section: Discussionsupporting
confidence: 89%
“…Of note, participants performed supervised high-intensity interval training in the latter study [ 9 , 10 ], whereas in the current study, they performed unsupervised continuous training [ 8 ], potentially explaining the divergent findings. However, in line with the data presented herein, tocilizumab significantly increased the serum adiponectin levels in patients with rheumatoid disease [ 11 , 12 ]. Of note, no placebo controls were included in the latter studies.…”
Section: Discussionsupporting
confidence: 89%
“…Another study showed increased adiponectin and reduced chemerin levels in RA patients after anti-IL-6 treatment in both monotherapy or combined therapy with methotrexate independent of the treatment response [ 51 ]. Another recent study showed that tocilizumab treatment of RA patients with active RA despite previous conventional synthetic disease-modifying antirheumatoic drug (DMARD) and/or biological DMARD treatment was associated with an increase in total and HMW adiponectin, especially early after treatment onset, then declining until month 6 to 12 [ 52 ]. In this study, anti-IL-6 treatment also induced a gain in lean mass, while fat mass remained unchanged.…”
Section: Adipokines In Autoimmune Rheumatoid Arthritismentioning
confidence: 99%
“…It was reported recently that after tocilizumab treatment for 24 weeks, resistin levels were significantly increased [ 66 , 78 ]. However, regarding anti-IL-6 treatment with tocilizumab of patients with active RA despite previous csDMARDS and/or bDMARDs, no significant changes in systemic resistin along with leptin and ghrelin during follow-up after 12 months were observed in contrast to adiponectin [ 52 ]. In addition, resistin was found not to be associated with the metabolic syndrome (by National Cholesterol Education Program’s ATP III and clinical parameters) at baseline and after one year of treatment of RA patients with DMRDs [ 63 ].…”
Section: Adipokines In Autoimmune Rheumatoid Arthritismentioning
confidence: 99%
“…Conversely, chronic inflammation during RA is associated with persistent elevations of IL6 and insulin resistance and with an increased risk of metabolic syndrome even in patients of normal weight [ 20 ]. A few studies have investigated the effect of tocilizumab on body composition [ 4 , 21 , 22 ]. In a 1 year open follow-up study including 21 active RA patients [ 4 ], a significant increase in lean mass was observed without changes for body fat mass.…”
Section: Discussionmentioning
confidence: 99%